Toxoplasmosis: a silent opportunistic diseases in HIV/AIDS patients - Sim, B.L.H.; Khairul Anuar, A.; Nissapatorn, V.; Lee, C.K.C.; Lim, Y.A.L.; Tan, K.S.; Jamaiah, I.; Rohela, M.; Ahmad, A.; Hadita, S.; Lott, P.W.; Ng, K.T.; et al. (2007)
A total of 693 HIV/AIDS patients were recruited in this retrospective and descriptive study during April 2003 to December 2004, Hospital Kuala Lumpur, Malaysia. It was found that both genders were shown to be within the same range of age (M = 18-79 vs F = 18-73), while a median age was slightly higher in male (36 years) than female (31 years). The majority of both genders were significantly shown in the age group of 25 to 34 years, but a higher rate was evident in females (42) (p = 0.001). It was even observed that male patients were mainly Chinese (44.7) and single (57.3) (p = 0.001), while the females were Chinese (40.6) and married (83.3) (p = 0.000). However, the highest numbers of both genders were manifested to be heterosexuals (M = 47.6 vs F = 86.2), followed by intravenous drug users (M = 39.3 vs F = 6.5) (p = 0.000). The range of CD4 cell count was 0 to 1799 with a median of 230 cells/mm3. The level of CD4 cell count of < 200 cells/mm3 was significantly found in males (48.5) and between 200 to 499 and â¥500 cells/mm3 were 36.2 and 26.8 in females, respectively (p = 0.001). Overall, the Toxoplasma seroprevalence was 43.85 where seropositive of anti-Toxoplasma antibody relatively higher in males (50) than in females (37.7) (p = 0.015). Toxoplasma seropositivity was thoroughly evident among Malays (168; 51.1), Intravenous Drug Users (IDUs) and patients with toxoplasmic encephalitis (TE) (p = 0.001). Furthermore, anti-retroviral therapy including HAART was more significantly found in patients with 9 seropositive Toxoplasma when compared to 2 seronegative and unknown serostatus patients (p = 0.025). Seventeen AIDS-related toxoplasmic encephalitis patients were diagnosed at the time of this study, depicting hemiparesis as the most common neurological manifestation in 11 (64.7) patients, followed by headache and seizure in 6 (35.3) and 3 (17.7) patients, respectively. Interestingly, CT scan finding showed mass like structure with multiple (58.8), ring enhancing lesions (100), in parietal region (58.8) and edema (29.4) in these patients. Overall, the treatment outcome showed that 13 (76.5) patients had completed treatment with maintenance, whereas, 3 (17.6) patients were lost to follow up and 1 (6) patient was transferred to another hospital. No relapse or death case was reported during the time of this study.